2019
DOI: 10.1002/jbm.b.34330
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel organic–inorganic composite bone cements with high compressive strength, in vitro bioactivity and cytocompatibility

Abstract: In this work, novel bioactive organic–inorganic composite bone cements consisting of tricalcium silicate (C3S), sodium alginate (SA), and calcium sulfate hemihydrate (CS) were successfully fabricated for the first time via a special method designing material composition and internal structure simultaneously, which was intended to enhance mechanical performance by combining progressive hydration process of C3S with distinctive gelation capacity of SA and further improve degradability and self‐setting properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Ideal bone substitutes not only provide structural repair and mechanical support for bone to a certain extent, but also promote bone regeneration by stimulating favorable attachment, proliferation, and osteogenic differentiation of bone-related cells. The C 3 S/SA/ CS composite cements with superior physicochemical properties had been successfully designed and fabricated in our previous study 16 and were further illustrated to enhance osteogenic performances in vitro and in vivo in the present study. Thus, proliferation, attachment, and osteogenic differentiation of BMSCs treated Relative mRNA expression 0.8 with C 3 S/SA/CS, as well as bone regeneration in vivo, were investigated in detail to evaluate the osteogenic performances of composite cements.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Ideal bone substitutes not only provide structural repair and mechanical support for bone to a certain extent, but also promote bone regeneration by stimulating favorable attachment, proliferation, and osteogenic differentiation of bone-related cells. The C 3 S/SA/ CS composite cements with superior physicochemical properties had been successfully designed and fabricated in our previous study 16 and were further illustrated to enhance osteogenic performances in vitro and in vivo in the present study. Thus, proliferation, attachment, and osteogenic differentiation of BMSCs treated Relative mRNA expression 0.8 with C 3 S/SA/CS, as well as bone regeneration in vivo, were investigated in detail to evaluate the osteogenic performances of composite cements.…”
Section: Discussionmentioning
confidence: 88%
“…via forming ionic bridges between adjacent polymer chains. 14,15 Thereby, in our previous study, 16 we had successfully designed and fabricated ternary organic-inorganic composite bone cements (tricalcium silicate/sodium alginate/calcium sulfate hemihydrate, C 3 S/SA/CS) with special dual-network structure via combining C 3 S hydration with SA gelation, and preliminarily demonstrated that the C 3 S/SA/CS composite cements possessed high compressive strength, proper setting time, good injectability, appropriate degradability, and excellent in vitro bioactivity, all of which could be adjusted by modulating the compositions for specific clinical application. For these above reasons, it is quite necessary to make more in-depth research on the osteogenic performances in vitro and in vivo of the C 3 S/SA/CS composite cements.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…To perform weight-loss tests, samples with a diameter and height of 6 and 7 mm, respectively were soaked in a phosphate buffer solution (PBS) with a surface area to solution volume ratio of 0.1 cm 2 /mL. 14,15 The PBS was refreshed every week, and the pH value of each solution was determined using a pH meter (PHS-3C, Shanghai instrument electric science instrument Co. Ltd, China) at days 1, 3, 7, 14, 28, and 42. Thereafter, the samples were removed after the respective incubation periods, and the discs were dried in a 60°C vacuum drying oven for 24 h. The original samples, which were not soaked in PBS but dried directly, were used as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in the Dulbecco’s modified eagle medium (DMEM) containing 10% fetal bovine serum and stored in incubator with 5% CO 2 and 95% relative humidity at 37 °C [ 35 ]. Before the cell culture experiment, all cement discs (Φ 6 mm × 3 mm) were sterilized at 160 °C for 8 h. The C 3 Ss and Fe/C 3 Ss discs were immersed in DMEM for 3 days at 4 °C to prepare ion extracts, and the solid to liquid ratio was 0.2 g/mL [ 36 ]. The cultured cells were planted in the extract for 24, 48 and 72 h, respectively, to evaluate the cell proliferation abilities and toxicity tests of the materials.…”
Section: Methodsmentioning
confidence: 99%